Vitamin C and E Treatment Blunts Sprint Interval Training–Induced Changes in Inflammatory Mediator-, Calcium-, and Mitochondria-Related Signaling in Recreationally Active Elderly Humans - Victoria L. Wyckelsma; Tomas Venckunas; Marius Brazaitis; Stefano Gastaldello; Audrius Snieckus; Nerijus Eimantas; Neringa Baranauskiene; Andrejus Subocius; Albertas Skurvydas; Mati Pääsuke; Helena Gapeyeva; Priit Kaasik; et al. (Antioxidants, 2020)
Sprint interval training (SIT) has emerged as a time-efficient training regimen for young individuals. Here, we studied whether SIT is effective also in elderly individuals and whether the training response was affected by treatment with the antioxidants vitamin C and E. Recreationally active elderly (mean age 65) men received either vitamin C (1 g/day) and vitamin E (235 mg/day) or placebo. Training consisted of nine SIT sessions (three sessions/week for three weeks of 4-6 repetitions of 30-s all-out cycling sprints) interposed by 4 min rest. Vastus lateralis muscle biopsies were taken before, 1 h after, and 24 h after the first and last SIT sessions. At the end of the three weeks of training, SIT-induced changes in relative mRNA expression of reactive oxygen/nitrogen species (ROS)- and mitochondria-related proteins, inflammatory mediators, and the sarcoplasmic reticulum Ca2+ channel, the ryanodine receptor 1 (RyR1), were blunted in the vitamin treated group. Western blots frequently showed a major (>50%) decrease in the full-length expression of RyR1 24 h after SIT sessions; in the trained state, vitamin treatment seemed to provide protection against this severe RyR1 modification. Power at exhaustion during an incremental cycling test was increased by ~5% at the end of the training period, whereas maximal oxygen uptake remained unchanged; vitamin treatment did not affect these measures. In conclusion, treatment with the antioxidants vitamin C and E blunts SIT-induced cellular signaling in skeletal muscle of elderly individuals, while the present training regimen was too short or too intense for the changes in signaling to be translated into a clear-cut change in physical performance.